A high‐resolution record of Holocene climate and vegetation dynamics from the southern Cape coast of South Africa: pollen and microcharcoal evidence from Eilandvlei - Lynne J. Quick; Brian M. Chase; Michael Wündsch; Kelly L. Kirsten; Manuel Chevalier; Roland Mäusbacher; Michael E. Meadows; Torsten Haberzettl (Journal of Quaternary Science, 2018)
The southern Cape is a particularly dynamic region of South Africa in terms of climate change as it is influenced by both temperate and tropical circulation systems. This paper presents pollen and microcharcoal data generated from a sediment core extracted from the coastal lake Eilandvlei spanning the last ∼8900 years. With an average sample resolution of 57 years, this record represents the highest resolution record of Holocene vegetation change from the region. The data indicate that cool, seasonal and moderately dry conditions characterized the Wilderness Embayment from ∼8900 to 8000 cal a BP . Afrotemperate forests expanded from ∼8000 cal a BP until 4700 cal a BP . This humid period is followed by indications of more arid and seasonal conditions until 3500 cal a BP . A long‐term increase in forest taxa suggests steadily increasing moisture availability across the late Holocene. Strong affinities are noted with records from more tropical regions of South Africa, suggesting that tropical systems are of importance in maintaining higher moisture availability in the region. An important mechanism of climate change is the Agulhas Current, which transmits what appears to be a localized signal of tropical variability to the southern Cape coast.